PERTUMBUHAN DAN PERKEMBANGAN TANAMAN Gmelina moluccana (RE-NUMERASI KEDELAPAN) - Erick Max Leimena; Febian Filiph Tetelay; Moda Talaohu (JURNAL HUTAN PULAU-PULAU KECIL, 2023)
This research aims to determine the annual growth rate, diameter growth, and technical rotation age achievement of Titi trees (Gmelina moluccana) 8 years after planting. The method employed is a quantitative descriptive approach, involving the re-measurement (re-numeration) of Titi trees to calculate growth rates and observe changes in growth stages. The results of the study indicate a current annual increment (CAI) of 2.69 cm/yr for diameter in the eighth year, and a mean annual increment (MAI) of 1.52 cm/yr for diameter. In terms of height, the current annual increment (CAI) is 2.48 cm/yr in the eighth year, with a mean annual increment (MAI) of 1.49 cm/yr. The achievement of the technical rotation age for Titi trees (Gmelina moluccana) based on diameter growth is reached in the seventh year. In the eighth year, the development of Titi trees (Gmelina moluccana) shows that 23 individuals are still at the pole stage, 52 individuals have reached the tree stage, and there are no trees that have flowered or fruited yet.